Armet is an effector protein mediating aphid‐plant interactions. Issue 5 (12th February 2015) - Wang, Wei; Dai, Huaien; Zhang, Yi; Chandrasekar, Raman; Luo, Lan; Hiromasa, Yasuaki; Sheng, Changzhong; Peng, Gongxin; Chen, Shaoliang; Tomich, John M.; Reese, John; Edwards, Owain; et al.
ABSTRACT: Aphid saliva is predicted to contain proteins that modulate plant defenses and facilitate feeding. Armet is a well‐characterized bifunctional protein in mammalian systems. Here we report a new role of Armet, namely as an effector protein in the pea aphid, Acyrthosiphon pisum. Pea aphid Armet's physical and chemical properties and its intracellular role are comparable to those reported for mammalian Armets. Uniquely, we detected Armet in aphid watery saliva and in the phloem sap of fava beans fed on by aphids. Armet's transcript level is several times higher in the salivary gland when aphids feed on bean plants than when they feed on an artificial diet. Knockdown of the Armet transcript by RNA interference disturbs aphid feeding behavior on fava beans measured by the electrical penetration graph technique and leads to a shortened life span. Inoculation of pea aphid Armet protein into tobacco leaves induced a transcriptional response that included pathogen‐responsive genes. The data suggest that Armet is an effector protein mediating aphid‐plant interactions.—Wang, W., Dai, H., Zhang, Y., Chandrasekar, R., Luo, L., Hiromasa, Y., Sheng, C., Peng, G., Chen, S., Tomich, J. M., Reese, J., Edwards, O., Kang, L., Reeck, G., Cui, F. Armet is an effector protein mediating aphid‐plant interactions. FASEB J. 29, 2032‐2045 (2015). www.fasebj.org